Gambaran tingkat kepuasan pasien peserta BPJS dan pasien umum terhadap pelayanan di faskes tingkat pertama poli gigi Puskesmas IV Denpasar Selatan - I Gusti Ayu Sri Wulan W; Ni Kd Fiora Rena Pertiwi; Mia Ayustina Prasetya (School of Dentistry Faculty of Medicine Udayana University, 2019)
Introduction: Satisfaction of patient is one of main indicators of health facility. The increase of healthcare quality must be done by the healthcare unit including Puskesmas (Public Health Center) in facing the globalization era. One of efforts in increasing the healthcare quality is by measuring the satisfaction level of the patient. The aim of the study is to describe the satisfaction level of BPJS participants dental patients and general dental patients with the services provided in Puskesmas IV South Denpasar. Method: This research is a descriptive study. Sample of research is the BPJS participants and general patients and patients that received services in Puskesmas IV South Denpasar as much 84 people with the details of 42 general patients and 42 BPJS participants patients. The collecting of data by using questionnaire. Results: The results showed that the general patients and BPJS participants patients expect get satisfactory service with a percentage of 100%. In fact the general patients and BPJS participants patient. who expressed his satisfaction based on five dimensions of service quality is: Reliability 88.10% for general patients and 92.86% for BPJS participants patient, Responsiveness 78.57% for general patients and 64.29% for BPJS participants patient, Assurance 66.67% for general patients and 59.52% for BPJS participants patient, Empathy for general patients amounted 76.19% and 35.71% for BPJS participants patient and Tangibles 78.57% for general patients, 95.24% for BPJS participants patient. Conclusion: Based on this study results, it can be concluded that the general level of patient satisfaction and BPJS participants patient amounted to 82.12%, as very satisfied with the services obtained in Puskesmas IV South Denpasar. The analizing result show the p score is 0,22 > 0,05. Which mean, there is no significant.